Trends of Instructional Design Development: A Bibliometric Analysis - Zahid Zufar At Thaariq; Alif Hanifatur Rosyidah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Instructional design, as part of educational technology, is very useful in planning the desired direction of teaching and learning activities. Designers need to have a direction that can relate to the rapid development of the times. Researchers conducted a bibliometric study to review the current direction of instructional design development. This study is characterized by being analytical across time, as it is based on analyzing files in the time period (2013-2023) collected in Google Scholar database of 1000 articles. Then the article data obtained was analyzed to see what retention had developed. The results of the review show that there are various instructional design directions relevant to various constructs, such as (1) online learning, (2) blended learning/instruction, (3) project-based learning, (4) gamification, (5) instructional modules, (6) computer-assisted learning, and (7) simulation-based learning. These four results have signaled that the current paradigm is within the scope of e-learning. These results can be used as an illustration for educators and other designers to see the latest emerging instructional design trends.Desain pembelajaran, sebagai bagian dari teknologi pendidikan, sangat berguna dalam merencanakan arah kegiatan belajar mengajar yang diinginkan. Desainer perlu memiliki arah yang dapat berhubungan dengan perkembangan zaman yang begitu cepat. Peneliti melakukan studi bibliometrik untuk meninjau arah pengembangan desain pembelajaran saat ini. Studi ini memiliki karakteristik analitis lintas waktu, karena didasarkan pada analisis file dalam periode waktu (2013-2023) yang dikumpulkan dalam basis data Google Scholar sebanyak 1000 artikel. Kemudian data artikel yang diperoleh dianalisis untuk melihat retensi yang telah berkembang. Hasil tinjauan menunjukkan bahwa terdapat berbagai arah desain pembelajaran yang direlevansikan dengan berbagai konstruk, seperti (1) online learning, (2) blended learning/instruction, (3) project-based learning, (4) gamifikasi, (5) modul pembelajaran, (6) pembelajaran berbantuan komputer dan (7) pembelajaran berbasis simulasi. Keempat hasil tersebut telah menandakan bahwa paradigma saat ini telah berada pada lingkup pembelajaran berbasis elektronik (e-learning). Hasil ini bisa dijadikan sebagai gambaran bagi pendidik maupun desainer lainnya dalam melihat tren desain pembelajaran terkini yang telah berkembang.